The effect of direct learning method according to the theory of the summons scheme in learning some basic tennis skills - Muhammad Hussein Muhammad, Qusay; Mohammed Abbood, Ruaa (International Journal of Psychosocial Rehabilitation, 2020)
The importance of the research came to emphasize the importance of kinetic learning methods and their role in learning about tennis as it helps the learner to upgrade the skill side according to each type of these methods and also shows us the most effective and important in transferring the correct information during performance. The research problem was that there is a fluctuation in learning basic skills in tennis that does not rise to the level of ambition, which is caused by the difficulty in choosing the best method for learning the skills under study, and this requires us to experiment and investigate the scientific facts of these types of learning methods and a course to learn basic skills in tennis.